Hyperbaric Oxygen Therapy Associated with Ventricular–Subcutaneous Shunt Promotes Neuroprotection in Young Hydrocephalic Rats. (15th April 2022) - da Silva, Stephanya Covas; da Silva Beggiora, Pâmella; Catalão, Carlos Henrique Rocha; Dutra, Maurício; Matias Júnior, Ivair; Santos, Marcelo Volpon; Machado, Hélio Rubens; da Silva Lopes, Luiza
Graphical abstract: Highlights: Hippocampal preservation helped better performance on memory tests in HBOT groups. HBOT associated with shunt increases the expression of the antioxidant enzyme SOD1. Joint therapies preserve total and replicating cells in GM and the neuronal viability. HBOT associated with derivation reduced apoptosis via Caspase-3 in the cortex. Better myelin preservation in periventricular white matter in HBOT groups. Abstract: Hydrocephalus is characterized by the accumulation of CSF within the cerebral ventricles and the subarachnoid space. Ventricular volume can progressively increase and generate serious damage to the nervous system, with cerebral hypoxia/ischemia as one of the most important factors involved. Hyperbaric oxygen therapy (HBOT) improves oxygen supply to tissues, which can reduce the progression of lesions secondary to ventricular enlargement. We evaluated whether HBOT associated with CSF diversion can promote neuroprotective effects to structures damaged by ventriculomegaly and understand its role. Seven-day-old male Wistar Hannover rats submitted to hydrocephalus by intracisternal injection of 15% kaolin were used. The animals were divided into six groups, with ten animals in each: control, control associated with hyperbaric therapy, hydrocephalic without treatment, hydrocephalic treated with hyperbaric oxygen therapy, hydrocephalic treated with CSF deviation, and hydrocephalic treated with hyperbaric oxygen therapy associated with CSF deviation. To assess the response to treatment, behavioral tests were performed such as modified Morris water maze and object recognition, evaluation by transcranial ultrasonography, histology by Hematoxylin–Eosin and Luxol Fast Blue, immunohistochemistry for GFAP, Ki-67, Caspase-3, COX-2, NeuN and SOD1, and biochemical ELISA assay for GFAP and MBP. The results show that the association of treatments exerts neuroprotective effects such as neurobehavioral improvement, preservation of periventricular structures, antioxidant effect, and reduction of damage resulting from ischemia and the neuroinflammatory process. We conclude that HBOT has the potential to be used as an adjuvant treatment to CSF deviation surgery in experimental hydrocephalus.